The Association Between IL‐8 Gene Polymorphisms and the Risk of Several Types of Cancer, Especially in Gastric Cancer - Bin Xu; Yidan Yan (Cancer Reports)
ABSTRACT Background Changes in functional genetic polymorphisms may increase or decrease the risk of cancer in patients. Nowadays, the association between polymorphisms in the interleukin‐8 (IL‐8) gene and the susceptibility of cancer risk have been investigated in many studies, however, above relationships remain unclear. Aim The current study aims to comprehensively evaluate the association between IL‐8 gene six polymorphisms and the whole cancer risk, especially −251 polymorphism and gastric cancer. Methods and Results Six polymorphisms (−251, −353, +678, +1633, +2767, +781) were collected. The expression of serum IL‐8 was calculated by ELISA assay. First, 104 case–control studies were conducted. Second, this research has made significant discoveries regarding the −251, −353 and +781 polymorphisms and the potential associations with cancer risk. Finally, the serum IL‐8 levels in gastric cancer patients with AA/TT genotypes were significantly higher than those with the same genotypes of healthy controls and TT genotypes in gastric cancer patients. Conclusion Overall, the investigation has revealed that IL‐8 gene polymorphisms significantly influence vulnerability to cancer development, especially for gastric cancer.